Santa Catarina : Disaster Risk Profiling for Improved Natural Hazards Resilience Planning - World Bank (Washington, DC, 2017)
This report seeks to further the body of disaster risk management (DRM) knowledge in Santa Catarina by identifying flood asset exposure risks and consequently empower the state government and its institutions to include DRM practices and information in their daily operations and decision-making processes, respectively. In this context, a novel study was jointly designed and developed by the World Bank and Santa Catarina’s state government with the ultimate aim to produce a state-level Catastrophe (CAT) model. The novelty and depth of the study allowed the team to draw a number of potential policy implications and possible decision making to improve the state’s resilience to natural disasters. To the best of the team’s knowledge, this is a first-of-its-kind study in Brazil and has potential direct applications to a wide body of professions and institutions in Santa Catarina. Finally, the proposed methodological approach was heavily based on the national census as well as on commonly accessible hydro-meteorological data and topographic information to ensure replicability in other Brazilian states or municipalities.